Pengaruh Penggunaan Media Plastisin/Playdough Terhadap Kreativitas Anak Usia Dini di TK Mabdaul Falah Kelompok B Pesisir Kaduara Timur Sumenep - Evin Oktania Ariska (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
This study aims to determine the effect of the uses of plasticine / playdough media on the creativity of young children in kindergarten Mabdaul Falah group B East Kaduara Coastal Sumenep and how much influence on children's creativity. This type of research is a Quantitative Research method of product moment correlation, because product moment correlation is method used to determine the level of relationship between two or more variables. Data collection techniques from this research are Questionnaire and Test. The location of this research was conducted in Mabdaul Kindergarten Falah Coastal East Kaduara Sumenep. The subjects of this study were group B with 17children, consisting of 5boys and 12 girls.The results showed that there was an influence of the use of plasticine / playdough media on children's creativity. This is indicated by obtaining a positive value of r work value of 0.655. Value of "r"work which is equal to 0.655 is greater than r criticism of product moment both in 95% confidence interval and 99% confidence interval, where the 95% confidence interval is 0.482 and in the 99% confidence interval is 0.606. So "r"work>"r"table and indicate that the work is significant, where there is an influence of the use of plasticine / playdough media on children's creativity. And it is also known that the value of "r"work which is worth 0.655 is between 0.40-0.70. This means that variable X (Use of Plasticine / Playdough Media) and variable Y (Child Creativity) have sufficient relationships / correlations.